hyperactivity disorder in school going children aged between 5-12 years in Bengaluru. Current Pediatric Research. 21(2):321-326. Sam Richa, JihaneRohayem, RabihChammai, Francois Kazour, Ramzi Haddad, Sani Hleis, Abbas Alameddine, Bernard Gerbaka. 2012. AD - P.M. MEERA, C.L.SHARON*, SEEJA THOMACHAN, E.R. ANEENA and P.S. LAKSHMY (The Journal of Research ANGRAU, 2021)
Probiotics are increasingly being added to food products in order to develop functional foodswith health promoting effects. Hence, an attempt was made to develop a probiotic drink containingpassion fruit and mango involving L. acidophilus.In the study, five treatments (along with one control)with three replications were standardized. The most acceptable combination (50% Passion fruit + 50% Mango) of the drink was pasteurised at 800C for 20 minutes and allowed to cool. The pasteuriseddrink was then inoculated with 4ìl L.acidophilus and incubated for a period of one hour at 370C whichhad availability of 13. 35 log cfu g-1.The probiotic passion fruit based drink along with its control(nonprobioticdrink) had TSS content of 12.50 and 13.20 0Brix, titratable acidity of 1.98 % and 1.60 % ,total sugar 16.66 and 17.10 g 100 g-1, reducing sugar 4.08 and 4.40 g 100 g-1, protein 0.70 and 0.36g 100 g-1, carbohydrate 13.32 and 14.72 100 g-1, energy of 56.08 and 60.32 Kcal, ascorbic acid of 10mg 100 g-1 and 13.7 mg 100 g-1and total ash 1.60 % and 1.52 %, respectively.